Estudo Técnico-Econômico da Produção de Etileno com zero emissões de Escopo 1 e 2 de CO2 - Ferro, Felipe Bressani (Universidade Federal de São Carlos, 2025)
Given the global context of concerns about climate change and the impacts caused by human actions on the atmosphere, it is necessary to reflect on the development of technologies that reduce the impact of industries regarding the emission of greenhouse gases, such as CO2. Knowing this, and with the development of incentives for companies that invest in technologies to reduce CO2 emissions, such as carbon credits, studies are being conducted to develop new technologies capable of meeting this demand, as ethylene industries, on average, emit 0.5 kg of carbon dioxide for each kg of ethylene produced. Thus, an analysis was developed for the construction of an ethylene production plant that will use hydrogen instead of natural gas as fuel, which aims to save about 1 million tons of CO2 annually from scope 1 and 2, with an initial investment of 3.5 billion dollars, resulting in a 2 billion loss in a scenario projected 25 years ahead.
Technical and Economic Study of Ethylene Production with zero Scope 1 and 2 CO2 emissions
Keywords: Produção de Etileno; Emissões de carbono; Sustentabilidade; Créditos de carbono; Ethylene production; Carbon emissions; Sustainability; Carbon credits; ENGENHARIAS::ENGENHARIA QUIMICA::PROCESSOS INDUSTRIAIS DE ENGENHARIA QUIMICA